79 EXPERIENCES OF DIRECTORS OF NURSING IN RESIDENTIAL CARE OF OLDER PEOPLE DURING COVID 19. (25th October 2022) - Phelan, A; Louise, D; Alice, C; Kent, S; Naughton, C; Tuohy, D; Ryan, A; Byrne, M
Abstract: Background: COVID-19 was a global public health crisis and deaths in the over 65 age group represented a disproportionate number of deaths in older people. In particular, nursing homes experienced clusters of infection and high mortality rates. This paper discusses experiences of care homes' Directors of Nursing/Persons in Charge (DoN) in their preparedness, management and control of care during COVID-19. Methods: A mixed methods approach was used (survey- n=122) and semi-structured interviews (n=20) were conducted with DoNs in private and voluntary older person care homes in the Republic of Ireland. Survey data was analysed using descriptive and inferential statistics. Interviews were analysed using Braun & Clarke's thematic analysis. Results: DoNs demonstrated an initial challenge in protecting residents from infection and also managing infection outbreak. However, over time they experienced more effectiveness in managing infection prevention and control as demanded at the level of a pandemic. Fifty percent of respondents experienced an infection outbreak and the data does not demonstrate any significant difference in preparedness and management in care homes which had outbreaks and those who had no outbreaks. Other challenges were related to financial sustainability of their facility while 47% of DoNs were either actively seeking other work, or thinking of leaving their post. In the interviews, the DoNs spoke of persistent concerns with the well-being of the staff and residents and a constant worry about meeting regulatory requirements and ensuring adequate staff cover for residents care needs. Moreover, the DoNs spoke of the difficulties when the media sensationalized poor care leading to a reduction of public confidence in the sector. Conclusion: The DoNs were under constant alert and although had acclimatized to high level of infection control and prevention and managing emerging issues, the strain of the pandemic remained evident. Recommendations are given related to care homes and related to system level management for future public health crisis.